1990
DOI: 10.1007/bf02580943
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein profile in type II diabetic patients with and without coronary heart disease

Abstract: Diabetes mellitus is frequently associated with lipid metabolism abnormalities. In the present study the lipid and apolipoprotein profiles have been compared in type II diabetic subjects with (n = 30) and without (n = 30) coronary heart disease (CHD). All subjects were studied after good metabolic control had been achieved. Significant differences in plasma lipids and apolipoproteins were seen in diabetic patients with CHD in comparison with diabetics without CHD. Patients with CHD presented higher total chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Similar findings were recently reported from other laboratories, showing, among other things, that the levels of plasma apoB, apoC-lll (40,41), and apoE (40) are higher in diabetic patients with vascular disease than in patients without vascular disease. It was, therefore, of considerable interest to determine the levels of apoB-containing lipoprotein families and their possible relationship to vascular disease.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings were recently reported from other laboratories, showing, among other things, that the levels of plasma apoB, apoC-lll (40,41), and apoE (40) are higher in diabetic patients with vascular disease than in patients without vascular disease. It was, therefore, of considerable interest to determine the levels of apoB-containing lipoprotein families and their possible relationship to vascular disease.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies (5-9, [13][14][15] indicate that, in addition to LDL cholesterol level, this dyslipidemia is an important CVD risk factor in individuals with diabetes. Although the CVD risk associated with individual lipoproteins has been examined, it would be valuable to have a measure that reflects the combined risk of all lipoprotein changes observed in diabetes.…”
mentioning
confidence: 98%
“…It is the first study which investigates this correlation and we suggested a synergic action between MMPs and apolipoproteins in cardiovascular complications. In previous studies, Apo‐CIII and Apo‐E have been associated with a higher risk of diabetes 46 ; their blood levels were increased in chronic heart disease (CHD) in relation to dyslipoproteinaemia 47 and they were elevated in CAD 48 . High Apo‐CIII level was found in CAD patients, 49 as well as in patients with familial hyperlipidemia and cardiovascular disease 50 .…”
Section: Discussionmentioning
confidence: 91%
“…Apo-E have been associated with a higher risk of diabetes 46 ; their F I G U R E 4 Heatmap showing study biomarkers and the associated discrimination between patient and control groups blood levels were increased in chronic heart disease (CHD) in relation to dyslipoproteinaemia 47 and they were elevated in CAD. 48 High Apo-CIII level was found in CAD patients, 49 as well as in patients with familial hyperlipidemia and cardiovascular disease. 50 Apo-CII and Apo-E were higher in function of stenosis progression.…”
Section: Discussionmentioning
confidence: 99%